2019
DOI: 10.1093/ntr/ntz206
|View full text |Cite
|
Sign up to set email alerts
|

Five-Day Changes in Biomarkers of Exposure Among Adult Smokers After Completely Switching From Combustible Cigarettes to a Nicotine-Salt Pod System

Abstract: Introduction This study examined changes in biomarkers of exposure (BoE) after 5 days of nicotine-salt pod system (NSPS) use, compared with continuation of usual-cigarette smoking and cigarette abstinence, among adult combustible cigarette smokers. Aims and Methods A randomized, open-label, parallel-cohort, confinement study of healthy adult smokers, naive to NSPS use, was conducted. Participants (N = 90) were randomized to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 33 publications
3
69
0
Order By: Relevance
“…Tobacco smokers who switch completely to e-cigarettes significantly reduce their levels of exposure to known cigarette toxicants, as shown recently in a 5-days trial by the manufacturer (Jay et al 2019). A closed system device with a low power setting has the advantage that toxicant generation is comparatively low and no easy manipulation by the consumer is feasible as with open systems.…”
Section: Discussionmentioning
confidence: 93%
“…Tobacco smokers who switch completely to e-cigarettes significantly reduce their levels of exposure to known cigarette toxicants, as shown recently in a 5-days trial by the manufacturer (Jay et al 2019). A closed system device with a low power setting has the advantage that toxicant generation is comparatively low and no easy manipulation by the consumer is feasible as with open systems.…”
Section: Discussionmentioning
confidence: 93%
“…Two were experimental studies, one quasi-experimental and two were cross-sectional. In terms of study quality, two of the five studies were funded by commercial interests in ENDS use/tobacco [33, 34]. Nevertheless, a particular advantage of one of these was that it kept users in a controlled environment (albeit only for five days) [33], which may have reduced the risks of contamination via undeclared dual use of ENDS use and tobacco products, as well as exposure to secondhand smoke/ENDS aerosol from others.…”
Section: Resultsmentioning
confidence: 99%
“…Lower volatility may also facilitate greater lung exposure and absorption of nicotine rather than buccal absorption 21 , offering quicker and more efficient nicotine transport to the brain. Indeed, in the past year, two studies have demonstrated that e-cigarettes with nicotine salt formulations (nicotine lactate and nicotine benzoate) can achieve nicotine absorption equivalent to that of conventional cigarettes, although the nicotine e-liquid concentrations investigated were up to 48 mg/ mL and 59 mg/mL, respectively 11,22 , which are considerably higher than the limits set by some regulatory bodies.…”
mentioning
confidence: 94%